ATTITUDE OF PHYSICIANS TOWARDS MEDICAL FINANCIAL DECISION-MAKING: NAVIGATING THE INTERSECTION OF ECONOMICS AND HEALTHCARE - Sorongon, Chris G.; Madrigal, Dennis V.; Yuesti, Anik (EMAS: Jurnal Ekonomi, Manajemen dan Bisnis, 2025)
This paper explores the role of financial physicians (medical professionals with expertise in financial management) in integrating economic principles into clinical practice. As healthcare systems globally face pressures to contain costs while improving patient outcomes, financial physicians are pivotal in shaping sustainable medical decision-making. A mixed-methods approach, combining surveys and interviews with financial physicians from various specialties, was used to evaluate their attitudes towards financial and clinical decision-making. The study examines themes such as the importance of cost-efficiency, the ethical implications of financial constraints in patient care, and the balance between clinical judgment and economic realities. Preliminary findings show that while financial physicians recognize the necessity of economic considerations for healthcare sustainability, they express concerns about potential conflicts with clinical integrity and patient-centered care. The study reveals a dichotomy: financial physicians support informed decision-making that includes cost considerations but emphasize protecting patient welfare from economic biases. Additionally, the study identifies barriers such as resistance from traditional medical paradigms and lack of interdisciplinary collaboration. Recommendations include enhancing health economics training for medical professionals and fostering collaboration between financial and clinical teams. Ultimately, this research highlights the crucial role of financial physicians in navigating the complexities of medical decision-making, aiming to optimize healthcare delivery and improve patient outcomes while ensuring system sustainability.